2022
DOI: 10.3390/antibiotics11070849
|View full text |Cite
|
Sign up to set email alerts
|

Review of Antimicrobial Resistance in Wastewater in Japan: Current Challenges and Future Perspectives

Abstract: Antimicrobial resistance (AMR) circulates through humans, animals, and the environments, requiring a One Health approach. Recently, urban sewage has increasingly been suggested as a hotspot for AMR even in high-income countries (HICs), where the water sanitation and hygiene infrastructure are well-developed. To understand the current status of AMR in wastewater in a HIC, we reviewed the epidemiological studies on AMR in the sewage environment in Japan from the published literature. Our review showed that a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 73 publications
(201 reference statements)
0
13
0
Order By: Relevance
“…This suggests that the current spread of MRSA in Japan is not limited to medical institutions, but may be widespread throughout the city as already mentioned [ 16 , 17 , 18 ]. Although the degree of pollutant loading from hospital effluent to STP influent varies greatly from region to region and country to country [ 73 , 74 , 75 , 76 , 77 , 78 ], our results support the need for further conclusive research by taking regional customs, bias, and unknown factors into consideration. In addition, due to the presence of a wide variety of live microorganisms in activated sludge in the biological treatment reactors at STPs [ 79 ], there have been concerns that AMRB could result in a pool of AMRB through zygotic transmission or transformation [ 80 , 81 , 82 ].…”
Section: Discussionmentioning
confidence: 46%
“…This suggests that the current spread of MRSA in Japan is not limited to medical institutions, but may be widespread throughout the city as already mentioned [ 16 , 17 , 18 ]. Although the degree of pollutant loading from hospital effluent to STP influent varies greatly from region to region and country to country [ 73 , 74 , 75 , 76 , 77 , 78 ], our results support the need for further conclusive research by taking regional customs, bias, and unknown factors into consideration. In addition, due to the presence of a wide variety of live microorganisms in activated sludge in the biological treatment reactors at STPs [ 79 ], there have been concerns that AMRB could result in a pool of AMRB through zygotic transmission or transformation [ 80 , 81 , 82 ].…”
Section: Discussionmentioning
confidence: 46%
“…About 25% of wastewater treatment systems in Japan are combined sewer systems that carry both untreated wastewater and rainwater simultaneously. Combined sewer systems pose a high risk of causing environmental contamination, especially during heavy rains and flooding events, which have become more pronounced because of climate change [ 19 ]. However, there are no regulations limiting the discharge of antimicrobial resistance (AMR), and the actual amount of AMR is unknown, highlighting a potential gap in environmental monitoring and regulation.…”
Section: Antibiotic Resistance (Abr) In Aquatic Environmentsmentioning
confidence: 99%
“…In recent years, antimicrobial resistance (AMR) has become dangerously close to our daily lives, raising concerns about sustainable human development [1][2][3]. A significant issue with AMR is that it not only poses a direct health risk of infecting people through hospital-and community-acquired infections, but also an indirect risk of infecting humans via the environment [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) has proposed the "One Health" approach as a comprehensive measure for humans-animals-environment and has called for the formulation of national action plans in each country [8]. In Japan, action plans have been established and measures are progressing [2,9]. Previous research has indicated the impact of AMR originating from wastewater entering the environment, despite the fact that the origins of AMR detected in aquatic environments are diverse [3,10,11].…”
Section: Introductionmentioning
confidence: 99%